Measurements of line intensities for some lines of methyl iodide in the ν5 and ν3 + ν6 bands. (December 2018) - Boughdiri, A.; Manceron, L.; Maaroufi, N.; Rotger, M.; Aroui, H.
Highlights: The line intensities of the ν5 and ν3  +  v 6 bands of CH3 I are measured for the first time. The vibrational transition dipole moment, the Herman–Wallis parameters as well as the band strengths have been retrieved. The measured line intensities were reproduced with a mean value of difference of about 7%. Analysis of the overlapped line using the Rosenkranz profile demonstrates a negligible line-mixing effect. Abstract: The line intensities for R R - and P P - sub-branch transitions in the ν5 and ν3  +  v 6 bands of CH3 I are measured for the first time for 270 lines with 5 ≤  J  ≤ 40 and 4 ≤  K  ≤ 11 using a multi-pressure fitting method with a Voigt profile. Seven spectra have been recorded using the Bruker IFS125HR Fourier Transform Spectrometer at the AILES beamline of SOLEIL Synchrotron with a resolution of 0.002 cm −1 for pressures between 0.270 and 2.433 mbar. Line intensities are analyzed and discussed as a function of the rotational quantum numbers. On average, the accuracy of the measured data is estimated to be about 4.5% for the two bands. The measured line intensities have been used to derive the vibrational transition moment, the Herman–Wallis parameters as well as the intensities of the two bands. The values for the band strengths of the ν5 and ν3  +  v 6 are respectively 46.47 ± 2.63 cm −2  atm −1 and 14.79 ± 1.60 cm −2  atm −1 . The measured line intensities were reproduced with mean values of difference of about 8.3% and 3.8% for the ν5 and ν3  +  v 6 bands respectively. At pressure used in this work, analysis of the overlapped line using the Rosenkranz profile demonstrates a negligible line-mixing effect on line intensities.